Pengaruh Tipe Kultur Kontainer pada Keberhasilan Pembentukan Embrio Somatik Kakao - Nur Ajijah; Cici Tresniawati; Syafaruddin Syafaruddin (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Container culture have an important role in determining the success of in vitro culture since it will affect the development of culture, such as the formation of embryonic structures. The study aimed to determine the effect of culture container types on cacao somatic embryogenesis. The study was conducted at Tissue Culture Laboratory, Superior Seed Development Unit of IAARD, Bogor, from April to September 2016. The tests were conducted on the effect of container and explant types as well as the effect of container types and genotypes. The effects of container and explant types were tested using callus induced from petal and staminoid explants of Sca 6, whereas the effects of container types and genotypes were tested using callus induced from petal explants of Sca 6 and ICCRI 4. Afterwards, the somatic embryos were induced using petri dishes or culture bottles according to treatment. The results showed no significant interaction between container and explant types on the average percentage of the formation and number of somatic embryos (10.28% embryos/explants in culture bottles and 7.89% embryos/explants in petri dishes). Meanwhile, there was significant interaction between genotypes and container types in the initial period of somatic embryos formation (15 and 18 weeks after culture), but the effect was not significant in the final period of observation (21 weeks after culture). The results indicate that culture bottles, which have lower prices, can be used to replace petri dishes to induce the formation of somatic embryos in cacao.